ORIENTASI POLITIK PEMILIH PEREMPUAN DALAM PEMILIHAN UMUM LEGISLATIF KOTA BUKITTINGGI TAHUN 2019 - Meggi Azhari; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research begins with the emergence of the phenomenon in the city of Bukittinggi, that in the 2019 legislative elections there were a majority of women in each electoral district of Bukittinggi, but only two women were elected. The author examines this phenomenon in order to describe and analyze the Political Orientation of Women Voters in the Legislative Election of Bukittinggi City in 2019. This study provides an objective picture of the political orientation of women voters. The political orientation of the female voters referred to in this study is how the orientation of the female voter thinks to choose or make a choice to a candidate in the 2019 Legislative General Election in Bukittinggi City. This orientation includes three aspects, namely cognitive, affective, and evaluative.            In this study, the authors used a quantitative approach to the type of descriptive research. The sample selection is done by area sampling technique. The measurement scale in this study uses a Likert scale. Data collection techniques are carried out by giving questionnaires directly to respondents to be answered. The data obtained is then presented in tabular form and discussed descriptively according to the existing theory.            The results showed that there was no influence on the number of female voters with women candidates being elected. The Political Orientation of Women Voters in the Legislative Election of Bukittinggi City in 2019 was influenced by the similarity of their hometown, residential area, religion and ethnicity with legislative candidates. Women voters in making their choices are purely their own choices, meaning that they are not influenced by others, whether they are husbands, immediate family members or local traditional leaders. Keywords: Political Orientation, Women's Voters, Legislative Elections